Constructing anhydrous proton exchange membranes through alternate depositing graphene oxide and chitosan on sulfonated poly(vinylidenefluoride) or sulfonated poly(vinylidene fluoride-co-hexafluoropropylene) membranes. (5th January 2021) - Shen, Si; Jia, Tingting; Jia, Jing; Wang, Ning; Song, Di; Zhao, Jing; Jin, Jin; Che, Quantong
Graphical abstract: Highlights: Proton exchange membranes were prepared through depositing chitosan and graphene oxide. Methanol permeability was (2.26–3.46) × 10 −7 cm 2 /s. Proton conductivity reached 2.34 × 10 −1 S/cm at 140 °C under anhydrous condition. Abstract: The proton exchange membranes (PEMs) have been constructed through alternate depositing chitosan (CS) and graphene oxide (GO) on the membrane substrates of sulfonated poly(vinylidenefluoride) (SPVDF) or sulfonated poly(vinylidene fluoride-co-hexafluoropropylene) (SPVDF-HFP). Phosphoric acid (PA) doped membranes were formed owing to the intermolecular hydrogen bonds, which were expected to work as PEMs in high temperature proton exchange membrane fuel cells (HTPEMFCs). The prepared layer-by-layer (LBL) depositional composite membranes showed the fine capacity to combine PA molecules with the lower dimension swelling. As expected, SPVDF(CS/GO)50 /PA and SPVDF-HFP(CS/GO)50 /PA membranes respectively exhibited higher proton conductivity values of 2.34 × 10 −1 S/cm and 1.56 × 10 −1 S/cm at 140 °C. Furthermore, the proton conductivity values of 3.52 × 10 −1 S/cm and 2.25 × 10 −1 S/cm at 140 °C in a 500-hour non-stop test could correspond to the negligible leakage of the depositional layers from the composite membranes. Because the doped PA molecules entered the gaps between the depositional layers, the prepared PA doped membranes possessed the enhanced mechanical strength owing to the compacted structure. Most interestingly, the prepared LBL deposited membranes could retain the better tensile stress even if PA molecules were doped with the formation of SPVDF(CS/GO)50 /PA and SPVDF-HFP(CS/GO)50 /PA membranes. Meanwhile, the proper thermal stability, methanol permeability and proton conductivity stability of the prepared membranes could suggest that the strategy of alternate depositing the functional components on membrane substrates is substantially more effective at improving the grade of PEMs. In our opinion, the fine balance on proton conductivity and mechanical property could make them stand out from other candidates as PEMs for HTPEMFCs.